Two Distinct Bacterial Biofilm Components Trigger Metamorphosis in the Colonial Hydrozoan Hydractinia echinata - Huijuan Guo (American Society for Microbiology, 2021)
Bacterial biofilms profoundly influence the recruitment and settlement of marine invertebrates, critical steps for diverse marine processes such as the formation of coral reefs, the maintenance of marine fisheries, and the fouling of submerged surfaces. However, the complex composition of biofilms often makes the characterization of individual signals and regulatory mechanisms challenging.